Maternal mortality in the indigenous and non-indigenous population in Pará: contribution to the surveillance of deaths - Deivid Ramos dos Santos; Laura Maria Vidal Nogueira; Bárbara Lopes Paiva; Ivaneide Leal Ataide Rodrigues; Lívia Félix de Oliveira; Samantha Pereira Caldas (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: To analyze the occurrence of Maternal Mortality in general and in the indigenous population in the state of Pará. Method: A quantitative, analytical and retrospective study was performed, covering a historical series from 2005 to 2014. For the analysis of the results, non-parametric statistical tests, the Chi-square test and the G test were processed in the BioStat 5.0 software program. Results: A total of 884 maternal deaths were reported in the state of Pará, corresponding to a Mortality Rate of 60.7 per 100,000 live births for non-indigenous women and 135.8 per 100,000 live births for indigenous women. Oedema, proteinuria and hypertensive disorders in pregnancy, childbirth and puerperium corresponded to 30.5% (n = 270). Conclusion and Implications for the Practice: Maternal mortality remains a serious public health problem in the state of Pará, clearly demonstrating that indigenous pregnant women require greater care, since they showed higher Maternal Mortality Rates when compared to non-indigenous women.